Estimated timing of the first menstrual period and dietary and nutritional correlates of menarche among urban school‐going adolescents in four sub‐Saharan African sites - Janaína Calu Costa; Anne Marie Darling; Sachin Shinde; Amare W. Tadesse; Huda Sherfi; Mary Mwanyika‐Sando; Amani Tinkasimile; Deepika Sharma; Till Baernighausen; Wafaie W. Fawzi (Maternal and Child Nutrition, 2025)
Abstract Characterizing the timing of menarche and the factors that are associated with it is important for understanding a population's reproductive health needs and long‐term health trajectories. We estimated the age at the menstrual onset among adolescent girls and the association between dietary and nutritional factors and menarche in four sub‐Saharan African urban sites. We used cross‐sectional school‐based data from 2307 female adolescents aged 10–14 years collected by the Africa Research, Implementation Science, and Education (ARISE) Network in Ouagadougou, Burkina Faso; Addis Ababa, Ethiopia; Khartoum, Sudan; and Dar es Salaam, Tanzania. Logit models were used to estimate the median age at menarche at each site. Associations between menarche and BMI‐for‐age, stunting, dietary quality and food insecurity across settings were assessed using Poisson regression models adjusted for country and school levels. The estimated median age at menarche was 13.1 years (95% confidence interval: 12.7, 13.5) in Ouagadougou; 12.9 (12.6, 13.2) in Addis Ababa; 13.3 (12.7, 13.6) in Khartoum; and 13.2 (12.3, 14.0) in Dar es Salaam. Between 18% and 49% of the girls in each setting had already menstruated. Based on the pooled multivariable models, underweight participants were 42% less likely (adjusted prevalence ratio [PR] 0.58 [0.44, 0.77]) to have experienced menarche in comparison to normal‐weight individuals. The likelihood of experiencing menarche increased for overweight [PR 1.47 (1.30,1.66)] and obese [PR 1.57 (1.35,1.82)] in comparison to normal‐weight girls. Those stunted were 47% less likely to have experienced menarche [PR 0.53 (0.41, 0.69)] than their nonstunted counterparts. A lower likelihood of menarche among those experiencing moderate/severe hunger when compared to those with no/little hunger was also observed (PR 0.78 [0.63,0.96]). No evidence of association with dietary quality was found. Further research is needed to strengthen the body of evidence and inform evidence‐based initiatives in low‐ and middle‐income settings.